Auricular acupuncture for shoulder pain: A protocol for systematic review and meta-analysis. Issue 17 (30th April 2021) - Hou, Xinju; Xiong, Wei; Lin, Xingzhen; Zhu, Yu; Yang, Ruifeng; Huang, Jiayang; Chen, Ziyin; Ma, Hongmei
Abstract: Background: Shoulder pain is a common problem in outpatient medical practice. Recent studies show that acupuncture has therapeutic effect on releasing symptoms of shoulder pain. The aim of this systematic review and meta-analysis is to access the efficacy and safety of auricular acupuncture for shoulder pain. Methods: Eight databases will be searched for randomized controlled trials of auricular acupuncture in the treatment of shoulder pain with retrieval time up to September 2020, including PubMed, Embase, The Cochrane Library, Web of science, CNKI, VIP, CBM, and Wangfang Data databases. We will evaluate the methodological quality of the included studies by using Cochrane Risk of Bias tool and conduct data analysis with Review Manager Software. Results: The results of this study will be disseminated through a peer-reviewed journal publication. Conclusion: The systematic review will provide up-to-date evidence for the efficacy and safety of auricular acupuncture in treating shoulder pain. PROSPERO registration number: CRD 42021238797 Abstract : Supplemental Digital Content is available in the text